РОЛЬ ПОСТРОЕНИЯ ПАРТНЕРСКИХ ОТНОШЕНИЙ С КЛИЕНТАМИ В БАНКАХ ВТОРОГО УРОВНЯ - Секенова, Д Е (Journal of Economic Research & Business Administration, 2015)
For today it is important to banks to find effective methods and tools of construction of long-term relations with loyal clients. One of possible and perspective methods of construction of partner relations in the market of bank services – marketing of relations. In given article partnership types in bank are considered an essence of construction of partner relations in bank sphere are shown.